Correction: Enhancing the selectivity of Nafion membrane by incorporating a novel functional skeleton molecule to improve the performance of direct methanol fuel cells. Issue 36 (14th September 2020) - Li, Jialin; Bu, Fanzhe; Ru, Chunyu; Jiang, Hao; Duan, Yuting; Sun, Yinan; Pu, Xingtong; Shang, Lichao; Li, Xifang; Zhao, Chengji
Abstract : Correction for 'Enhancing the selectivity of Nafion membrane by incorporating a novel functional skeleton molecule to improve the performance of direct methanol fuel cells' by Jialin Li et al., J. Mater. Chem. A, 2020, 8, 196–206, DOI: ; 10.1039/C9TA10215A .